Repercussões do Programa Institucional de Bolsa de Iniciação à Docência - PIBID - para a Filosofia no ensino médio - Gonçalves, Rita de Cassia Sant´ Anna de Athayde (2017)
The present study analyses the teaching of Philosophy and its relationship with the PIBID, seeking to comprehend the implications of the Institutional Program of Scholarship for Teaching Initiation – PIBID in the process of teaching of the Philosophy discipline in the secondary level. In this study it is intended the understanding to what extent the PIBID Philosophy appropriate itself of a Philosophy of the teaching of Philosophy, which has the potential to product significant effects for the students’ lives. It aims to understand the Philosophy and youth culture mediated by the actions of PIBID, so that the teaching of Philosophy is connected with the desires of the young, using, for this, the qualitative approach through bibliographic review. It is intended to examine how much the teaching practices exhibited in the PIBID Philosophy publications are pertinent to the cultural universe of the young person who attends secondary school today, as well as to analyze the teaching practices described by the subprojects PIBID Philosophy to understand if they are significant to the young person and in what proportion they present the potential to contribute to the reflection on their daily life. The corpus of research is constituted by the publications of the subprojects PIBID Philosophy, which narrate the theoretical investigations and the proposed actions for the teaching of Philosophy. With the intention of understanding what is essential to the teaching of Philosophy, the publications that present the theoreticalpractical reflections selected for analysis were classified into three categories. The first category attributes the identity of the teaching of Philosophy as derivative from the methodology adopted. The second considers that the teaching of Philosophy is defined by the contents chosen and the third bet that the teaching of Philosophy reaches its objectives when it has meaning for the young, independent of contents or methodologies. In the analyzes of the publications of the subprojects, it is verified that the PIBID Philosophy, through researches on the Philosophy of Teaching Philosophy, proposes conventional and unconventional activities that reject a teaching focused on the reproduction and the mechanical transmission of knowledge. Drawing on other areas of knowledge, the PIBID subprojects value interdisciplinarity so that the Philosophy makes sense for the young person, helping them to understand their experiences through a philosophical education. The PIBID contributes to the Philosophy class being philosophical, that is, that provides activities that allow the student to philosophize. Coherent with the performed research, it is concluded that the PIBID Philosophy develops a task which has been breaking resistances regarding the education model that prevents creative and problematizing thinking. The PIBID runs agaisnt the transmission and reproduction of knowledge and collaborates with the teaching of Philosophy in the school by creating new flows that give the young the possibility of daily problematizing the reality, their world, of understanding their experiences through Philosophy.